Theories of Religion Easily Introduced with A LIFE IN A TIN (UNA VITA IN SCATOLA Bruno Bozzetto, I 1967, 6’) - Pezzoli-Olgiati, Daria (Journal for religion, film and media, 2022)
A short animation film from the Sixties facilitates the access to theories of religion that react and conceptualise the changes of a decade that has largely influeced the way, we think of religion and the study of religion today.